CD38 deficiency leads to a defective short-lived transcriptomic response to chronic graft-versus-host disease induction, involving purinergic signaling-related genes and distinct transcriptomic signatures associated with lupus - Mercedes Zubiaur; Laura C. Terrón-Camero; Fernando Gordillo-González; Eduardo Andrés-León; Alicia Barroso-del Jesús; Luz María Canet-Antequera; María M. Pérez Sánchez-Cañete; África Martínez-Blanco; Marilú Domínguez-Pantoja; María Botia-Sánchez; Sonia Pérez-Cabrera; Nerea Bello-Iglesias; et al. (Frontiers in Immunology)
This study aimed to elucidate the transcriptomic signatures and dysregulated pathways associated with the autoimmune response in Cd38-/- mice compared to wild-type (WT) mice within the bm12 chronic graft-versus-host disease (cGVHD) lupus model. We conducted bulk RNA sequencing on peritoneal exudate cells (PECs) and spleen cells (SPC) at two and four weeks following adoptive cell transfer. We also analyzed cells from healthy, untreated mice. These analyses revealed a sustained upregulation of a transcriptional profile of purinergic receptors and ectonucleotidases in cGVHD WT PECs, which displayed a coordinated expression with several type I interferon-stimulated genes (ISGs) and with key molecules involved in the cyclic GMP-AMP synthase-stimulator of interferon genes (cGAS-STING) signaling pathway, two hallmarks in the lupus pathology. A second purinergic receptor transcriptomic profile, which included P2rx7 and P2rx4, showed a coordinated gene expression of the components of the NLRP3 inflammasome with its potential activators. These processes were transcriptionally less active in cGVHD Cd38-/- PECs than in WT PECs. We have also shown evidence of a distinct enrichment in pathways signatures that define processes such as Ca2+ ion homeostasis, cell division, phagosome, autophagy, senescence, cytokine/cytokine receptor interactions, Th17 and Th1/Th2 cell differentiation in Cd38-/- versus WT samples, which reflected the milder inflammatory and autoimmune response elicited in Cd38-/- mice relative to WT counterparts in response to the allogeneic challenge. Last, we have shown an intense metabolic reprogramming toward oxidative phosphorylation in PECs and SPC from cGVHD WT mice, which may reflect an increased cellular demand for oxygen consumption, in contrast to PECs and SPC from cGVHD Cd38-/- mice, which showed a short-lived metabolic effect at the transcriptomic level. Overall, these findings support the pro-inflammatory and immunomodulatory role of CD38 during the development of the cGVHD-lupus disease.